Răspuns :
|x-3| = |2x-3|
(1) x-3 = 2x-3 => -3+3 = 2x-x => 0 = x => x = 0
(2) -(x-3) = -(2x-3) => x-3 = 2x-3 => x = 0
(3) x-3 = -(2x-3) => x-3 = -2x+3 => x + 2x = 3+3 => 3x = 6 => x = 2
(4) -(x-3) = 2x-3 => x-3 = -(2x-3) => x = 2
S = {0; 2}
(1) x-3 = 2x-3 => -3+3 = 2x-x => 0 = x => x = 0
(2) -(x-3) = -(2x-3) => x-3 = 2x-3 => x = 0
(3) x-3 = -(2x-3) => x-3 = -2x+3 => x + 2x = 3+3 => 3x = 6 => x = 2
(4) -(x-3) = 2x-3 => x-3 = -(2x-3) => x = 2
S = {0; 2}
|x-3| = |2x-3|a) x-3 = 2x-3 ⇒ -3+3 = 2x-x ⇒ 0 = x ⇒ x = 0b) - (x-3) = - (2x-3) ⇒ x-3 = 2x-3 ⇒ x = 0c) x-3 = - (2x-3) ⇒ x-3 = - 2x+3 ⇒ x + 2x = 3+3 ⇒ 3x = 6 ⇒ x =6/3=2 d) - (x-3) = 2x-3 ⇒ x-3 = - (2x-3) ⇒ x = 2S= {0; 2}